1998
DOI: 10.1159/000069440
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of IFN-γ Increase in the Serum of HIV-Positive and Healthy Subjects after Subcutaneous Injection of a Non-Fermented <i>Viscum album</i> L. Extract

Abstract: Iscador®, an aqueous extract of Viscum album L., has been used for more than 80 years as an anticancer drug. Due to its immunomodulatory potential, since the onset of the AIDS epidemic it has also been applied in the treatment of HIV-positive and AIDS patients in the form of the preparation V. album QuFrF (VaQuFrF; Labor Hiscia, Arlesheim, Switzerland). In in vitro investigations, incubation of peripheral blood mononuclear cells with V. album L. extracts resulted in stimulation of lymphocyte activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, IFN-g increase in the serum of HIVpositive and healthy subjects was not noticed following subcutaneous injection of a non-fermented V. album extracts. 144 5.10. Anti-mutagenic V. album var.…”
Section: Anti-microbialmentioning
confidence: 99%
“…However, IFN-g increase in the serum of HIVpositive and healthy subjects was not noticed following subcutaneous injection of a non-fermented V. album extracts. 144 5.10. Anti-mutagenic V. album var.…”
Section: Anti-microbialmentioning
confidence: 99%
“…Due to the strong impact of mistletoe on the immune system, it was proposed that it might be useful as a complementary treatment of patients with human immunodeficiency virus (HIV). Studies to confirm the induction of immunomodulation and possibility of the inhibition of the progression of HIV disease are needed (Gorter et al 1996(Gorter et al , 1999Stoss and Gorter 1998;Stoss et al 1999). An in vitro study revealed that a phenolic glycoside, homoeriodictyol-7-O-β-D-glucopyranoside-4′-O-β-D-apiofuranoside, isolated from Viscum articulatum Burm.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…is toxic (Ogunmefun et al 2013). The compounds obtained from V. album are prevalently used for gastro-intestinal, diabetes, blood pressure problems, treatment of cancer, the hepatitis C virus (HCV), HIV, and human parainfluenza virus type 2 (HPIV-2) (Stoss & Gorter 1998, Tusenius et al 2001, Karagöz et al 2003, but the field of the use of the plant may vary based on the chemical properties of host tree which in turn affect compounds present in V. album.…”
Section: Introductionmentioning
confidence: 99%